"Faith Alone"—Primus Inter Pares: Welcome to the Banquet. (2nd September 2013) - Simpson, Gary M.
Abstract: Faith alone represents the primus inter pares of the sixteenth‐century Reformation's four solas . Gary Simpson introduces five authors who critically explore and creatively extend the doctrine of justification by faith alone as Dialog with its Fall issues (2013–2017) leans into the 500 th anniversary of the Reformation (2017).